Influence of school culture and classroom environment in improving soft skills amongst secondary schoolers - Ahmad, Abdul Razaq; Chew, Fong Peng; Zulnaidi, Hutkemri; Sobri, Kiagus Muhammad; Alfitri, - (Eskisehir Osmangazi University, 2019)
This study aimed to determine the influence of support from the school culture and classroom environment in improving soft skills amongst students. Moreover, the study explored different soft skills, school culture and classroom environments based on gender and type of schools. This study used a quantitative approach by using surveys to gather information. A total of 400 students from three different types of schools were chosen using random sampling. The three types of schools were National Secondary Schools, Religious Secondary Schools, and Technical and Vocational Secondary Schools around Selangor and Federal Territory of Kuala Lumpur. Data were analysed using SPSS 22.0 and AMOS 18. Results confirmed the distinctions of the school culture and classroom environments with the soft skills based on the gender and type of schools. SEM analysis corroborated that the school culture and classroom environment contributed to the development of soft skills. Therefore, schools should come up with programs and approaches to improve the soft skills amongst the students to be proficient in various fields in parallel with the rapid growth of the world. © 2019 Eskisehir Osmangazi University.